Teaching Descriptive Text Using Pictures to Improve Students’ Reading Comprehension - Desriani Nggolaon; Puput Eka Sari (English Education Study Program, 2020)
The purpose of this research is to know whether the pictures in descriptive text can improve students’ reading comprehension or not at the Tenth Grade Students in SMA Negeri 1 Luwuk. The research design in this research was quasi-experimental using non-equivalent control group design. The Independent variable of this research was pictures and the dependent variable was students’ reading comprehension. The Population of this research all students of IPA in SMA Negeri 1 Luwuk of the Tenth Grade were about 216 students, each class consisted of 36 students and the sample of this research were X MIPA 1 and X MIPA 2. The instrument used of this research was test. This research has two classes, experimental class and was control class. The data were taken by giving pre-test and post-test both of classes. The data indicated that, there was a significant difference between students’ pre-test and post-test in the experimental class. The mean score of students’ pre-test of experimental class was (57.02) and the mean score of post-test was (77.97). In experimental class, mean score of post-test was higher than mean score of pre-test. The result of the calculation statistical hypothesis test showed tvalue was higher than ttable (6.618 1.667) where the formula of significance level df = 005. Therefore, it was concluded that there was a significance effect of using pictures to improve student’ reading comprehension in teaching descriptive text at the Tenth Grade of SMA Negeri 1 Luwuk.Keywords: Pictures; Students’ Reading Comprehension; Descriptive text.